2006
DOI: 10.1016/j.laa.2006.01.009
|View full text |Cite
|
Sign up to set email alerts
|

On sufficient conditions for the total positivity and for the multiple positivity of matrices

Abstract: The following theorem is proved. Theorem. Suppose M = (a i,j ) be a k × k matrix with positive entries and a i,j a i+1,j+1 > 4 cos 2 π k+1 a i,j+1 a i+1,j (1 ≤ i ≤ k − 1, 1 ≤ j ≤ k − 1). Then det M > 0.The constant 4 cos 2 π k+1 in this Theorem is sharp. A few other results concerning totally positive and multiply positive matrices are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In [8] it is also shown that in the statement of Theorem A the constant c n is the smallest possible not only in the class of matrices with positive entries but in the classes of Toeplitz matrices and of Hankel matrices. We recall that a matrix M is Toeplitz matrix if it is of the form M = (a j−i ) and a matrix M is Hankel matrix if it is of the form M = (a j+i ).…”
Section: Then All Minors Of M Are Positivementioning
confidence: 97%
See 1 more Smart Citation
“…In [8] it is also shown that in the statement of Theorem A the constant c n is the smallest possible not only in the class of matrices with positive entries but in the classes of Toeplitz matrices and of Hankel matrices. We recall that a matrix M is Toeplitz matrix if it is of the form M = (a j−i ) and a matrix M is Hankel matrix if it is of the form M = (a j+i ).…”
Section: Then All Minors Of M Are Positivementioning
confidence: 97%
“…In [8] the authors of this note have proved that Theorem A remains valid if one replace the constantc by the constant c n := 4 cos 2 π n+1 . In [8] it is also shown that in the statement of Theorem A the constant c n is the smallest possible not only in the class of matrices with positive entries but in the classes of Toeplitz matrices and of Hankel matrices.…”
Section: Then All Minors Of M Are Positivementioning
confidence: 98%
“…We begin with a result of J. I. Hutchinson [64] that has been the subject of in vestigations by several authors: T. Craven and G. Csordas [39], D. K. Dimitrov [50], D. C. Kurtz [76], and O. M. Katkova and A. M. Vishnykova [70]. We begin with a result of J. I. Hutchinson [64] that has been the subject of in vestigations by several authors: T. Craven and G. Csordas [39], D. K. Dimitrov [50], D. C. Kurtz [76], and O. M. Katkova and A. M. Vishnykova [70].…”
Section: Higher Order and Iterated Turán And Laguerre Inequalitiesmentioning
confidence: 99%
“…In [4] it is also shown that the constant c m := 4 cos 2 π m+1 in the statement of Theorem A is the smallest possible not only in the class of m × m matrices with positive entries but in the classes of m × m Toeplitz matrices and of m × m Hankel matrices.…”
mentioning
confidence: 97%
“…By Sylvester's Criterion for positive definiteness we need to show that all leading principal minors of the matrix M Qp are positive. To do this we will use the following theorem from [4].…”
mentioning
confidence: 99%